Changes in force production and stroke parameters of trained able-bodied and unilateral arm-amputee female swimmers during a 30 s tethered front-crawl swim - Lee, C. J.; Sanders, R. H.; Payton, C. J. (Journal of Sports Sciences, 2015)
This study examined changes in the propulsive force and stroke parameters of arm-amputee and able-bodied swimmers during tethered swimming. Eighteen well-trained female swimmers (nine unilateral arm amputees and nine able-bodied) were videotaped performing maximal-effort 30 s front-crawl swims, while attached to a load cell mounted on a pool wall. Tether force, stroke rate, stroke phase durations and inter-arm angle were quantified. The able-bodied group produced significantly higher mean and maximum tether forces than the amputee group. The mean of the intra-cyclic force peaks was very similar for both groups. Mean and maximum tether force had significant negative associations with 100 m swim time, for both groups. Both groups exhibited a similar fatigue index (relative decrease in tether force) during the test, but the amputees had a significantly greater stroke rate decline. A significant positive association between stroke rate decline and fatigue index was obtained for the able-bodied group only. Inter-arm angle and relative phase durations did not change significantly during the test for either group, except the recovery phase duration of the arm amputees, which decreased significantly. This study`s results can contribute to the development of a more evidence-based classification system for swimmers with a disability.